Confirmation of a suspected 16q deletion in a dysmorphic child by flow karyotype analysis. Issue 2 (February 1987) - Cooke, A; Tolmie, J; Darlington, W; Boyd, E; Thomson, R; Ferguson-Smith, M A
Abstract : Cytogenetic examination of a dysmorphic infant with multiple congenital abnormalities revealed a possible de novo interstitial deletion in the long arm of chromosome 16. Conclusive proof of the deletion was obtained by flow karyotype analysis of the patient and both parents, which showed that the deleted segment was approximately 7000 kb in size.